2021
DOI: 10.3389/fpsyt.2021.665682
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii, Suicidal Behavior, and Intermediate Phenotypes for Suicidal Behavior

Abstract: Within the general literature on infections and suicidal behavior, studies on Toxoplasma gondii (T. gondii) occupy a central position. This is related to the parasite's neurotropism, high prevalence of chronic infection, as well as specific and non-specific behavioral alterations in rodents that lead to increased risk taking, which are recapitulated in humans by T. gondii's associations with suicidal behavior, as well as trait impulsivity and aggression, mental illness and traffic accidents. This paper is a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 347 publications
(436 reference statements)
0
17
0
Order By: Relevance
“…A recent casecontrol study also consistent with the above observations found a higher seroprevalence among schizophrenia patients especially in suicide attempters, against the control groups, and patients with no history of suicide attempts (Akgul et al, 2021) by emotional irritation (Gohardehi et al, 2018;Sutterland et al, 2019). In addition, numerous studies demonstrated T. gondii as a replicated risk factor in human psychiatric disorders such as unknown temporal lobe epileptic seizure (Ngoungou et al, 2015;Uzorka and Arend, 2017;Sadeghi et al, 2019), Alzheimer's disease (Bayani et al, 2019), cognitive impairment in several cognitive domains including short-term verbal memory and processing speed (Gale et al, 2015;de Haan et al, 2021), depression (Kamal et al, 2020), autism (Flegr and Horacek, 2019;Nayeri et al, 2020;Al et al, 2021), suicide and suicidal behavior (Kamal et al, 2020;Soleymani et al, 2020;Postolache et al, 2021), and other neurological disorders (Desmettre, 2020;Nayeri et al, 2021). Moreover, for human hosts, latent infection may also be associated with systemic changes in human personality (Lafferty, 2006).…”
Section: The Well-established Association Of Psychiatric Disorders In...mentioning
confidence: 99%
“…A recent casecontrol study also consistent with the above observations found a higher seroprevalence among schizophrenia patients especially in suicide attempters, against the control groups, and patients with no history of suicide attempts (Akgul et al, 2021) by emotional irritation (Gohardehi et al, 2018;Sutterland et al, 2019). In addition, numerous studies demonstrated T. gondii as a replicated risk factor in human psychiatric disorders such as unknown temporal lobe epileptic seizure (Ngoungou et al, 2015;Uzorka and Arend, 2017;Sadeghi et al, 2019), Alzheimer's disease (Bayani et al, 2019), cognitive impairment in several cognitive domains including short-term verbal memory and processing speed (Gale et al, 2015;de Haan et al, 2021), depression (Kamal et al, 2020), autism (Flegr and Horacek, 2019;Nayeri et al, 2020;Al et al, 2021), suicide and suicidal behavior (Kamal et al, 2020;Soleymani et al, 2020;Postolache et al, 2021), and other neurological disorders (Desmettre, 2020;Nayeri et al, 2021). Moreover, for human hosts, latent infection may also be associated with systemic changes in human personality (Lafferty, 2006).…”
Section: The Well-established Association Of Psychiatric Disorders In...mentioning
confidence: 99%
“…Elderly women (aged 60 or above) are more prone to suicidal attempts when seropositive for T. gondii [108]. A detailed review involving three wide metaanalyses in different European countries on the associations between T. gondii serology and suicidal behavior reported a 39 to 57% elevation of odds of suicide attempts in T. gondii IgG-positive patients [109]. One case report showed that a depressed 32-year-old male did not respond to antidepressant therapy until he was treated for acute toxoplasmosis, suggesting a probable association between toxoplasmosis and depression [110].…”
Section: Toxoplasmosis Depression and Behavioral Changesmentioning
confidence: 99%
“…Toxoplasma gondii is an intracellular parasite that can infect most warm-blooded animals, where it may invade the central nervous system and provoke neuroinflammation and behavioral changes (for recent reviews, see Mendez and Koshy, 2017 ; Martinez et al., 2018 ; Chen et al., 2019 ; de Haan et al., 2021 ; Nasuhidehnavi and Yap, 2021 ; Nayeri et al., 2021 ; Postolache et al., 2021 ). It is estimated that approximately 30% of the world’s population is infected with this protozoan, but there is much greater prevalence in African and South American countries ( Agordzo et al., 2019 ; Karshima and Karshima, 2020 ; Rahmanian et al., 2020 ; de Lima Bessa et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%